Sustainability strategies among Balinese heritage ensembles - Hood, Made Mantle (Universiti Pendidikan Sultan Idris, 2014)
Heritage ensembles typically conjure up images of antique heirloom instruments accumulating cultural capital while being passed down through generations. While that is the case for many historically significant gamelan orchestras on the island of Bali in Indonesia, the age of instruments is not a qualifier for the heritage designation of two prominent gamelan gong gede ensembles in the island's central district of Gianyar. Here in the lower highlands of Gianyar are the communities of Jasan and Sebatu. The significance of the pair in the discourse on heritage orchestras lies in their partnership to maintain one of the largest and most significant repertoires on the island. The communities of Jasan and Sebatu each have their own respective gong gede acquired only in the late 1980s. Indeed their bronze gongs and metallophones are new compared to the royal court heritage ensembles found in Pemecutan in the municipality of Denpasar or the status of Batur's ensemble built upon more than a century of service to a state temple. But what they lack in historical heritage and musical instrument artefacts, they more than compensate through sustaining the largest repertoire, a crucial resource component in heritage management. In this essay, I explore discourses on music and sustainability and assess the strategies these communities utilize in maintaining ritual music ensembles. I first examine the background to heritage management through a discussion of Jeff Todd Titon's four-tiered approach to sustainability in music. Then I provide ethnographies of individuals involved in a community partnership that draws on multiple resources, including musical notation, Bali's lucrative handicraft industry, and the sanctity of religious ritual to shore up heritage ensembles. Throughout I argue that while heritage may often constitute a top-down designation, it is also a label worn by insider stewards of tradition who consciously sustain music traditions from periphery positions.